THE BEGINNING OF GENETICS: GREGOR MENDEL AND OTHERS - Помогайбо, В.М.; Петрушов, А.В.; Березан, О.І. (World of Medicine and Biology, 2016)
The overview of the publications of the XIX and early XX century touching studying of heredity of living organisms was presented. Some researchers have observed the following same results as Mendel, but they did not understand or ignored them because they was interested only the problems of species. The success of Mendel’s experiments in the discovery of the first laws of genetics was due to the fact that he had the intention to identify the patterns of trait inheritance and used for them mathematical methods. The science of the XIX century was not ready to accept these laws and only re-opening them on the verge of centuries gave beginning of a new department of biology – genetics.